Perinatal outcomes and intrahepatic cholestasis of pregnancy: a prospective study - Parihar, Sangeeta; Singh, Swatantar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Women with intrahepatic cholestasis of pregnancy (ICP) have an increased risk for postpartum haemorrhage, dyslipidaemia, preterm labour and operative interference. Fetus in ICP has been associated with an increased incidence of preterm labour, preterm prelabour rupture of membrane, fetal distress, abnormal CTG, meconium staining, spontaneous intrauterine death. The present study was done to evaluate the perinatal outcomes – maternal outcomes and fetal outcomes of ICP. Methods: This was a prospective observational study carried out in a tertiary care teaching hospital. Total 1100 pregnant women were screened during the study period. Patients with ICP were identified in maternity care units after eliciting history about itching. Pregnancies with pregnancy induced hypertension and other liver diseases in pregnancy were excluded. Results: 62 pregnant women with prevalence rate of 5.64% have been found to be suffering from ICP. The most frequently affected (22, 35.48%) age-group with ICP were belong to age > 35 years. A majority of pregnant women with intrahepatic cholestasis of pregnancy was of multipara. ICP was highly significantly associated with small for gestational age (SGA, p-value: 0.0003); abnormal cardiotocography (CTG, p-value: 0.0002); and meconium stained liquor (p-value: 0.0001). Caesarean section as mode of delivery found significantly associated (p-value: 0.0033) with ICP. Insomnia (p-value: 0.0045); dyslipidemia (p-value: 0.0011); and postpartum haemorrhage (p-value: 0.0122) were also found significantly with ICP. Conclusions: ICP can adversely affect fetal as well as maternal pregnancy outcomes. Maternal outcomes have good prognosis, but fetal outcomes can be improved by timely and effective intervention.